Bride and the Groom covered in a veil - Mumbai Archive Project Team (Jio Institute, 2024)
The bride and the groom are covered in a veil while relatives perform aarti (the waving of a flame, usually from a lit lamp, before a deity during prayers), blessing the couple and welcoming the bride into the family.